A Novel MRI-Based Finite Element Modeling Method for Calculation of Myocardial Ischemia Effect in Patients With Functional Mitral Regurgitation - Zhang, Yue; Wang, Vicky Y.; Morgan, Ashley E.; Kim, Jiwon; Ge, Liang; Guccione, Julius M.; Weinsaft, Jonathan W.; Ratcliffe, Mark B. (Frontiers in Physiology, 2020)
Background: Functional Mitral Regurgitation (FMR) associated with coronary artery disease affects nearly 3 million patients in the United States. Both myocardial infarction (MI) and ischemia contribute to FMR development but uncertainty as to which patients will respond to revascularization (REVASC) of ischemia alone prevents rational decision making about FMR therapy. The aim of the study was to create patient-specific cardiac MRI (CMR) informed finite element (FE) models of the left ventricle (LV), calculate regional LV systolic contractility and then use optimized systolic material properties to simulate the effect of revascularization (virtual REVASC). Method: We describe a novel finite element method able to predict the effect of myocardial ischemia on regional left ventricular function. Cardiac MRI (CMR) was obtained in five patients with multi-vessel coronary disease and FMR before and 3 months after percutaneous REVASC and a single healthy volunteer. Patient-specific FE models were created and divided into 17 sectors where the systolic contractility parameter, T_max, of each sector was a function of regional stress perfusion (SP-CMR) and myocardial infarction (LGE-CMR) scores. Sector-specific circumferential and longitudinal end-systolic strain and LV volume from CSPAMM were used in a formal optimization to determine the sector based myocardial contractility, T_max, and ischemia effect, α. Virtual REVASC was simulated by setting α to zero. Results: The FE optimization successfully converged with good agreement between calculated and experimental end-systolic strain and LV volumes. Specifically, the optimized T_max for the healthy myocardium for five patients and the volunteer was 495.1 kPa, 336.8 kPa, 173.5 kPa, 227.9 kPa, 401.4 kPa, and 218.9 kPa. The optimized α was found to be 1.0, 0.44, and 0.08 for Patients 1, 2, and 3, and 0 for Patients 4 and 5. The calculated average of radial strain for the Patients 1, 2, and 3 at baseline and after virtual REVASC was 0.23 and 0.25, respectively. Conclusion: We developed a novel computational method able to predict the effect of myocardial ischemia in patients with FMR. This method can be used to predict the effect of ischemia on the regional myocardium and promises to facilitate better understanding of FMR response to REVASC.